Becoming your true self: Perceptions of authenticity across the lifespan. Issue 3 (4th May 2018) - Seto, Elizabeth; Schlegel, Rebecca J.
Abstract: Two studies investigated how authenticity is believed to change over time. We tested for two possible trajectories: (1) A simple positive linear progression driven by self-enhancement motives and (2) a linear progression followed by a plateau indicative of the end of the history illusion. Across both studies, participants completed measures of perceived authenticity for different points in their lives. Study 1 was over a relatively short period of time. Study 2 was over the course of the lifespan. Both studies revealed upward linear trends suggesting that participants believe they are becoming more authentic over time. Study 2 also revealed that people perceive particularly high rates of change in the recent past and near future. The preponderance of evidence favored the self-enhancement perspective.